Quartzite pebble technology in the final Middle Pleistocene of the Ribeira da Ponte da Pedra site (High Ribatejo, Central Portugal). (2017) - , Sara Cura; , Stefano Grimaldi; Cura, Pedro; Rosina, Pierluigi
No abstract available